PANDANGAN ORIENTALIS TERHADAP SUNNAH: Telaah Kritis atas Pandangan Goldziher - Iffah, Ummu (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This paper discusses the thought Goldziher about the authenticity of the Hadith. In this discussion will be seen how the great interest in themselves Goldziher on the study of the Sunnah of the Prophet Muhammad withvarious accusations and criticism which was unheard of in the ranks of scholars of Hadith for centuries, except of extremist groups who has long beenknown as anti tradition. In this paper the authors also attempted to show the weaknesses and errors of assessment Goldziher against the Hadith of the Prophet Muhammad.Keywords: Goldziher, authenticity, Hadith